Motivações para alimentação (não) saudável: contribuições dos valores humanos, imagem corporal e autocontrole - Santos, Layrtthon Carlos de Oliveira (2017)
This thesis aimed to know the motivations behind the healthy and unhealthy eating, developed two instruments to measure them and check how the self-control, human values and body image are related to them. Three chapters were developed. The Chapter 1 aimed to explore the motives related to the consumption of healthy and unhealthy foods in a Brazilian sample using a qualitative approach. Participants were 205 undergraduate students who answered a questionnaire with open questions about the reasons that led them to consume these foods. The Descending Hierarchical Classification analyzes results showed five motives related to consumption of healthy foods (weight loss, feel good, prevention of diseases, organismic needs and benefits) and other five to unhealthy foods (desire, various occasions, lack of time, practicality and advantages). The Chapter 2, divided in two steps, aimed to develop the Motivations for Healthy Eating Scale (MHES) and the Motivations for Unhealthy Eating Scale (MUES), and to gather evidence of their validity and accuracy. The step 1 was composed of 208 undergraduate students who answered the aforementioned measures. The exploratory factorial analysis results indicated a final structure of three factors for both MHES [Prevention of diseases (5 items, a = 0.93), Weight loss (5 items, a = 0.91) and Vitality (5 items, a = 0.91)] and MUES [Lack of time (5 items, a = 0.89), Desire (5 items, a = 0.89) and Social interaction (5 items, a = 0.83)]. From the step 2, 229 undergraduate students participated, who answered the final versions of MHES and MUES. The results of this study corroborated both the factorial model of MHES (CFI = 0.96, TLI = 0.95) and that of MUES (CFI = 0.95, TLI = 0.93), which were invariant in relation to the sex of the participants (?CFI < 0.010; ?RMSEA < 0.015). Finally, the Chapter 3 aimed to know the relationship between self-control, human values and body image with the motivations for healthy and unhealthy eating, as well as to develop explanatory models of these motivations. 391 people participated responding to measures of self-control, values, body image, body care and motivations. Overall, the results indicated that a higher level of self-control, social and central values and a higher satisfaction with body image are related to a higher motivation for healthy eating, while low self-control, personal values and lower satisfaction with body image are related to a greater motivation for unhealthy eating. The explanatory model of the motivations for healthy eating from self-control, social values and body care presented satisfactory adjustment indicators (CFI = 0.95, TLI = 0.93) that indicated the suitability of the model. In front of these results, it is certain that the objectives of the thesis have been achieved. The motivations for healthy and unhealthy eating were explored, developed two shorts and parsimonious instruments with great indicators of constructo validity and reliability, and the relations of these motivations with self-control, human values and body image were known. Certainly, these findings contribute to the literature on the subject.